The Correlation between Air Pollution Levels in East Jakarta and COPD Exacerbation at Persahabatan Hospital in 2019 - Habibi, Januar; Susanto, Agus Dwi; Ratnawati, Ratnawati (Respiratory Science, 2025)
Background: Air pollution has become a global environmental issue that has an impact on public health. Chronic obstructive pulmonary disease (COPD) is a chronic lung disease that can be caused by exposure to noxious gases and environmental factors. Cigarette smoke is a major risk factor for the development of COPD. However, several studies have shown that environmental exposures such as air pollution can contribute to the worsening of COPD. This study aimed to evaluate the correlation between the level of air pollution and exacerbation of COPD in East Jakarta in 2019. Method: This was a retrospective cohort study on COPD patients who experienced exacerbation in 2019 and came to the emergency room of Persahabatan National Respiratory Referral Hospital (PNRRH). Data was taken from the medical records by consecutive sampling. Data on the Index of Air Pollution Standards were obtained from the DKI Jakarta Provincial Environmental Service. Results: A total of 198 subjects met the inclusion criteria. Most of the subjects were male (92.4%), and the mean age was 63.39 years. Three pollutants had a positive correlation with COPD exacerbation rates, including PM10 (r=0.245), SO2 (r=0.497), and O3 (r=0.344). While the negative correlation were the levels of CO (r=-0.187) and NO2 (r=-0.366). However, the correlations were not statistically significant. Conclusion: PM10, SO2, and O3 are correlated with COPD exacerbations, whose visits to the emergency department of Persahabatan hospital. However, this correlation does not establish a cause-and-effect correlation because there are still other factors that trigger COPD exacerbations.